Juru Damai Dalam Penyelesaian Perselisihan Perkawinan Dengan Menggunakan Adat Di Negeri Pelauw - Tuankotta, Abdul Gani; Latupono, Barzah; Labetubun, Muchtar Anshary Hamid (BAMETI Customary Law Review, 2023)
Marriage is a bond, a very strong agreement, obedience to God's commands, so practicing it is worship, every marriage that is carried out ends until death is separated, but some are divorced a few moments later. The reasons for divorce vary, including financial, infidelity, jealousy, domestic violence (domestic violence), a moral crisis, one of the two cannot fulfill their respective obligations as husband and wife to form a family, and there may also be a violation of the rules. and marriage regulations Lack of understanding of purpose. If every couple knows and enforces this rule, and understands every implication of the goals of marriage, family happiness will be very easy to achieve, and far from divorce. The type of research used in this study is normative juridical, by examining legal materials in the form of primary legal materials, secondary legal materials, and tertiary legal materials and the legal analysis technique used is qualitative descriptive analysis. The result of the research is The traditional marriage procedure in Pelauw State starts from the process of proposing to the bride, the first day of the wedding is often referred to as Tifa night, namely a series of customs carried out by the bride, and the second day ma'asiwa sour, namely a series of customs carried out by the bride and groom from the family or the groom's traditional house brings the treasure to the bride's residence and then a few hours later the marriage ceremony takes place. The task of married brothers as peacemakers in resolving disputes is to examine the problems experienced by the husband and wife. So that they can summarize the problems they face and provide advice and peaceful efforts to the disputing parties.